2015 IEEE Topical Conference on Biomedical Wireless Technologies, Networks, and Sensing Systems (BioWireleSS) 2015
DOI: 10.1109/biowireless.2015.7152124
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of patterned vertical CNT for dry electrode sensing of physiological parameters

Abstract: Dry electrodes for impedimetric sensing of physiological parameters (such as ECG, EEG, and GSR) promise the ability for long duration monitoring. This paper describes the feasibility of a novel dry electrode interfacing using Patterned Vertical Carbon Nanotube (pvCNT) for physiological parameter sensing. The electrodes were fabricated on circular discs (φ = 10 mm) stainless steel substrate. Multiwalled electrically conductive carbon nanotubes were grown in pattered pillar formation of 100 µm squared with 50, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In our previous work we have fabricated many of pvCNT electrodes for dry impedimetric sensing [10,11]. The CNTs were grown in squared pillar patterns with a sufficient height to penetrate through the pores and the ridges of the Stratum Corneum of epidermis.…”
Section: Pvcnt Fapricationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work we have fabricated many of pvCNT electrodes for dry impedimetric sensing [10,11]. The CNTs were grown in squared pillar patterns with a sufficient height to penetrate through the pores and the ridges of the Stratum Corneum of epidermis.…”
Section: Pvcnt Fapricationmentioning
confidence: 99%
“…The low impedance electrode has the potential to reduce the noise during recording the physiological and neurological signals. We have previously shown that pvCNT have lower contact impedance than the traditional wet electrodes [10,11], however pvCNT electrodes suffered from the weakness of mechanically stable adherence to the substrate. Furthermore, even though small amount of CNT on dermis is not considered hazard, there is still risk of toxicity or skin reaction to CNT exposure.…”
Section: Introductionmentioning
confidence: 98%
“…The reported characteristics of the sensor are among the best in this field. An interesting way to create an EEG electrode is to use a patterned vertical carbon nanotube (pvCNT) [18]. Electrode made on the round discs (φ = 10 mm) made of stainless steel.…”
Section: Overview Of New Methods Ideas For the Development And Application Of Dry Electrodesmentioning
confidence: 99%
“…We have shown in previous work that the prototyped electrodes are developed such that the CNTs are grown in an aligned vertical pattern resulting in a bristle-like structure [41,42]. The pillar heights (~1.5 mm) are sufficient to measure the signal through hairy and rough areas of the skin.…”
Section: Pvcnt Fabricationmentioning
confidence: 99%
“…We have developed a dry electrode using pvCNT that has lower contact impedance than conventional wet electrodes [41][42][43]. This electrode is suitable for physiological and neurological signal acquisition with reduced noise.…”
Section: Introductionmentioning
confidence: 99%